Soil variability effect on the indices of potentially toxic elements pollution under the coffee (Coffea arabica)-enset (Ensete ventricosum) agroforestry systems of Southern Ethiopia - Abdelaali Ait Saghir; Ali Boularbah; Fisseha Asmelash; Fassil Kebede (Discover Applied Sciences)
Abstract Potentially toxic elements (PTEs) in agricultural soils pose serious environmental and health risks, necessitating accurate hazard assessments. This study investigated the extent, severity, and potential sources of PTEs in Cambisols, Luvisols, and Nitisols within the Gedeo Zone agroforestry systems, Ethiopia. Forty-six surface soil samples were analyzed using Inductively Coupled Plasma– Optical Emission Spectrometry (ICP-OES) to quantify the concentrations of Arsenic (As), Lead (Pb), Zinc (Zn), Copper (Cu), Manganese (Mn), Barium (Ba), Strontium (Sr), and Titanium (Ti). Quantitative indices including the Contamination Factor (Cf), Geo-accumulation Index (I-geo), Soil Pollution Index (SPI), and Enrichment Factor (EF), were computed. Results showed significant soil variability effects on PTEs distributions. Average concentrations (mg/kg) of PTEs were: Ti (4570.7), Mn (2358.3), Ba (229.8), Zn (102.8), Sr (43.0), Cu (24.4), Pb(13.6) and As(5.8). In addition, SPI values revealed localized moderate contamination for Pb (max SPI = 5.37 in Luvisols) and Zn (max SPI = 3.13 in Cambisols), and slight Cu contamination in Nitisols (SPI = 2.66). Moreover, As presented moderate contamination across all soil types, with the exception of Luvisols where SPI = 1.53 and I-geo = 2.29 were observed. EF confirmed that the sources of PTEs are of geogenic origin, although localized anthropogenic influences were detected, especially for Luvisols (EF = 3.4 and 2 for Zn and Pb respectively) likely due to the use of organic amendments. In conclusion, the findings highlight soil heterogeneity role in shaping PTEs risks, recommending soil-specific management practices and further research on phytoremediation potential using indigenous agroforestry species.